Protective Role of γδ T Cells in Different Pathogen Infections and Its Potential Clinical Application. (10th July 2018) - Zhao, Yueshui; Lin, Ling; Xiao, Zhangang; Li, Mingxing; Wu, Xu; Li, Wanping; Li, Xiaobing; Zhao, Qijie; Wu, Yuanlin; Zhang, Hanyu; Yin, Jianhua; Zhang, Lingling; et al.
Abstract : γδ T cells, a subgroup of T cells based on the γδ TCR, when compared with conventional T cells ( αβ T cells), make up a very small proportion of T cells. However, its various subgroups are widely distributed in different parts of the human body and are attractive effectors for infectious disease immunity. γδ T cells are activated and expanded by nonpeptidic antigens (P-Ags), major histocompatibility complex (MHC) molecules, and lipids which are associated with different kinds of pathogen infections. Activation and proliferation of γδ T cells play a significant role in diverse infectious diseases induced by viruses, bacteria, and parasites and exert their potential effector function to effectively eliminate infection. It is well known that many types of infectious diseases are detrimental to human life and health and give rise to high incidence of illnesses and death rate all over the world. To date, there is no comprehensive understanding of the correlation between γδ T cells and infectious diseases. In this review, we will focus on the various subgroups of γδ T cells (mainly V δ 1 T cells and V δ 2 T cells) which can induce multiple immune responses or effective functions to fight against common pathogen infections, such as Mycobacterium tuberculosis, Listeria monocytogenes, influenza viruses, HIV, EBV, and HBV. Hopefully, the gamma-delta T cell study will provide a novel effective way to treat infectious diseases.